2017
DOI: 10.1038/onc.2017.326
|View full text |Cite
|
Sign up to set email alerts
|

PTEN deficiency sensitizes endometrioid endometrial cancer to compound PARP-PI3K inhibition but not PARP inhibition as monotherapy

Abstract: Poly (ADP-ribose) polymerase (PARP) inhibitors have emerged as promising cancer therapeutics especially for tumors with deficient homologous recombination (HR) repair. However, as HR-deficient tumors represent only a small fraction of endometrial cancers, the therapeutic utility of PARP inhibitors is limited in this disease. Somatic loss of phosphatase and tensin homolog (PTEN), a tumor suppressor that counteracts phosphoinositide 3-kinase (PI3K) activity, is one of the most common genetic aberrations in endom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
77
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(85 citation statements)
references
References 48 publications
(73 reference statements)
7
77
1
Order By: Relevance
“…PTEN alterations are frequent in endometrial cancers, particularly in EEC and may modulate DSB-repair capacity by regulating the expression of RAD51 (20). In vitro studies have shown contradictory results, with some reporting no correlation between PTEN loss and HR deficiency (38,39), whereas others did find a correlation (40). In our study, we did not observe a correlation between HR capacity and IHC PTEN expression.…”
Section: Discussioncontrasting
confidence: 87%
“…PTEN alterations are frequent in endometrial cancers, particularly in EEC and may modulate DSB-repair capacity by regulating the expression of RAD51 (20). In vitro studies have shown contradictory results, with some reporting no correlation between PTEN loss and HR deficiency (38,39), whereas others did find a correlation (40). In our study, we did not observe a correlation between HR capacity and IHC PTEN expression.…”
Section: Discussioncontrasting
confidence: 87%
“…Although PTEN mutation was previously reported as a marker to predict sensitivity to PARP inhibitors, more recent evidence shows that PTEN mutation will cause an activation of the PI3K pathway. Hence, PTEN ‐mutated tumors would not respond to monotherapy of PARP inhibitors . Neither are PTEN ‐mutated tumors sensitive to platinum‐based treatment in chemotherapy .…”
Section: Discussionmentioning
confidence: 99%
“…PTEN-deficient tumor cells display a defect in HR due to defective expression and chromatin loading of RAD51 (12,16,43) and hence could be targeted by PARP inhibitors (30,43,44). In fact, PTEN deficiency sensitizes endometroid endometrial cancer to PARP inhibition alone (45) or in combination with PI3K pathway inhibition (46). In the present study, we confirmed these previous reports, but importantly, we found that Ishikawa EndoCA cells lacking nuclear PTEN are more sensitive to Olaparib, whereas cells with nuclear PTEN show an attenuated affect.…”
Section: Discussionmentioning
confidence: 99%